miR-29b-3p Inhibitor Alleviates Hypomethylation-Related Aberrations Through a Feedback Loop Between miR-29b-3p and DNA Methylation in Cardiomyocytes - Wu, Fang; Yang, Qian; Mi, Yaping; Wang, Feng; Cai, Ke; Zhang, Yawen; Wang, Youhua; Wang, Xu; Gui, Yonghao; Li, Qiang (Frontiers in Cell and Developmental Biology, 2022)
As a member of the miR-29 family, miR-29b regulates global DNA methylation through target DNA methyltransferases (DNMTs) and acts as both a target and a key effector in DNA methylation. In this study, we found that miR-29b-3p expression was inversely correlated with DNMT expression in the heart tissues of patients with congenital heart disease (CHD), but whether it interacts with DNMTs in cardiomyocytes remains unknown. Further results revealed a feedback loop between miR-29b-3p and DNMTs in cardiomyocytes. Moreover, miR-29b-3p inhibitor relieved the deformity of hypomethylated zebrafish and restored the DNA methylation patterns in cardiomyocytes, resulting in increased proliferation and renormalization of gene expression. These results suggest mutual regulation between miR-29b-3p and DNMTs in cardiomyocytes and support the epigenetic normalization of miRNA-based therapy in cardiomyocytes.